63-Year-Old Male with Gastric Outlet Obstruction - Bhavraj Khalsa; Patrick Rudersdorf; Dattesh Dave; Brian R. Smith; Chandana Lall (Case Reports in Radiology)
We describe a case of a 63-year-old male with complicated Bouveret’s syndrome, both in its presentation and in its management. Bouveret’s syndrome is a rare cause of gastric outlet obstruction resulting from mechanical obstruction from gallstones at the pyloroduodenal segment. As Bouveret’s syndrome can be a diagnostic and therapeutic challenge for clinicians, we aim to identify clinical and radiologic pearls that can lower the threshold for the diagnosis of Bouveret’s syndrome.